Susceptibility of Haemophilus ducreyi to spectinomycin in vitro. - Hafiz, S (1986)
Using an agar dilution technique with standardised inocula prepared by ultrasonication, the minimum inhibitory concentrations (MICs) of spectinomycin were determined for 66 strains of Haemophilus ducreyi, eight of which were beta lactamase producers. All strains were sensitive to concentrations of spectinomycin, which were well within the therapeutic ranges attained with normal dosage. The MIC50 and MIC90 were 8 mg/l, (range 0.007-16 mg/l).